Verhandlungen der Deutschen Gesellschaft für Innere Medizin. - Deutsche Gesellschaft für Innere Medizin.; Gesellschaft Deutscher Hämatologen.; Deutsche Gesellschaft für Rheumabekämpfung. (Verh dtsch ges inn med, 1921)
Consists of proceedings of the 33.-97. Kongress of the Deutsche Gesellschaft für Innere Medizin.
Volume 54 also found in Deutsches Archiv.
Suspended publication 1941-1947
Consists of proceedings of the 33.-97. Kongress of the Deutsche Gesellschaft für Innere Medizin.
Transactions of the 49th congress issued in cooperation with the Deutsche Gesellschaft für Rheumabekämpfung; the 58th congress, with the Gesellschaft Deutscher Hämatologen.
Generalregister: 21.-43. Kongress, 1904-31. 1 v.; 44.-69. Kongress, 1932-63. 1 v.
Keywords: Medicine. / [MeSH] / https://id.nlm.nih.gov/mesh/D008511; Medicine / Periodicals. / http://id.loc.gov/authorities/subjects/sh2008107665; Internal medicine / Congresses. / http://id.loc.gov/authorities/subjects/sh2008123995; Periodicals.